Islamic architecture in the Malay world : the mosque and other religious building - Kamaruddin Mohd. Ali 365416; International Seminar on Islamic Civilization in the Malay World (1989 : Bandar Seri Begawan) 478965 (Bandar Seri Begawan :, 1989)
02